Tanycytic Ependymoma: A Challenging Histological Diagnosis - Khaled M. Krisht; Meic H. Schmidt (Case Reports in Neurological Medicine)
Tanycytic ependymoma is a rare form of ependymoma that usually arises in the intramedullary spine. It has a unique histology emphasized by the inconspicuous ependymal pattern of cells and close resemblance to schwannoma and astrocytoma. The authors report a 50-year-old man with a cervical tanycytic ependymoma that was initially thought to be a schwannoma. The frozen histology section showed spindle cells with oval and elongated nuclei with occasional hemosiderin deposits present suggesting a preliminary diagnosis of schwannoma. Immunohistochemical staining of the permanent section revealed strong immunoreactivity for glial fibrillary acidic protein with intermittent S-100 positivity, confirming that the tumor was a tanycytic ependymoma. This underlines the challenges involved in making an accurate diagnosis and demonstrates that careful and detailed histological inspection with immunohistochemical stains and ultrastructural microscopy may be necessary to distinguish tanycytic ependymoma from other neoplasms.